Mother-infant bonding and postpartum depression during the COVID-19 pandemic - a risk for nurturing care and child development - Bárbara Portela Diniz; Sandra Josefina Ferraz Ellero Grisi; Danton Matheus de Souza; Ana Paula Scoleze Ferrer (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: The COVID-19 pandemic Increased the risk of impairing the mother-infant bonding. The objectives of this study were to evaluate the early bond established between mother and infant and postpartum depression (PPD) in pregnancies that occurred during the pandemic period, to identify the factors that may have influenced these outcomes and to verify if there was an association between bonding and probable PPD. Methods: This is a cross-sectional study of postpartum women from a public maternity hospital in the city of São Paulo conducted from February to June 2021, involving 127 mother-baby dyads. The initial data were collected in the immediate postpartum period and between 21-45 days after birth, using a semi-structured questionnaire on sociodemographic characteristics, gestational and birth conditions, and baby characteristics; the Edinburgh Postnatal Depression Scale (EPDS) and Postpartum Bonding Questionnaire (PBQ) were used to evaluate PPD and bonding, respectively. Results: The presence of probable PPD and unplanned pregnancies were associated with higher PBQ score and risk to impaired bonding (p = 0.001 and p = 0.004, respectively). EPDS showed a high prevalence of PPD (29.1%) and was not associated with any Studied variable. Probably, this high prevalence of probable PPD was due to the context of insecurity secondary to the pandemic. Conclusions: We observed an increase in the prevalence of probable PPD and unplanned pregnancies during the first 18 months of the pandemic, which were associated with worse scores in mother-infant bonding. The impaired bond can affect the future development of children born during this period.